Persepsi VisualPengunjung terhadap Elemen Interior Stilrod Café di Surabaya - Cynthia Siswanto; Andereas Pandu Setiawan (Intra, 2015)
This research about visual perception of British Interior-styled café at Surabaya aims to perceivehow the visual perception occurred while researcher in the thematic café through their applied interior design. This research was conducted in Surabaya with a case study of Stilrod Café as British Interior Design café. Qualitative-descriptive type research method is used in this research. Thecompiling data, literature-checking, interviews and direct observation to the object are necessary,whichthen followed by data analysis method then deduced into a conclusion. Results of the research become a case study of one thematic-British Interior Design-café style in Surabaya. Through this research, it is known how the customer’s visual perception about interior design of Stilrod Café.